2002
DOI: 10.1111/j.1365-2621.2002.tb09459.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Processing Conditions for Milk Coagulation Using the Hot Wire Method and Response Surface Methodology

Abstract: To evaluate the relationship between the factors affecting coagulation, the hot wire method was used for direct measurements of the renneting milk process as well as a central composite design with 3 factors: rennet concentration (x 1 ), renneting pH (x 2 ), and temperature (x 3 ). Second-order models for maximum voltage (Y 1 ), time at maximum voltage (Y 2 ), and coagulation time (Y 3 ) were employed to generate response surface contours. Optimum conditions for cutting time were found with x 1 = 0.0278 R.U./m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…A diffuse fiber optic near infrared (800 nm) reflectance sensor was also successfully tested by Payne, Hicks, and Shen (1993) and later by Laporte, Martel, and Paquin (1998) andLopez (2000, 2002) to monitor rennet coagulation of cows' and goats' milk, respectively. Different on-line techniques, based on optical systems (such as NIR diffuse reflectance or NIR transmission) or hot-wire technologies (Hori, 1985;Sbodio, Tercero, Coutaz, & Martinez, 2002), have also been compared with rheological techniques and validated by Payne (1999, 2000). Moreover, Passos et al (1999) observed a decrease in the thermal conductivity of milk during coagulation using a heated thermistor and established a good prediction equation for rennet coagulation time.…”
Section: Introductionmentioning
confidence: 99%
“…A diffuse fiber optic near infrared (800 nm) reflectance sensor was also successfully tested by Payne, Hicks, and Shen (1993) and later by Laporte, Martel, and Paquin (1998) andLopez (2000, 2002) to monitor rennet coagulation of cows' and goats' milk, respectively. Different on-line techniques, based on optical systems (such as NIR diffuse reflectance or NIR transmission) or hot-wire technologies (Hori, 1985;Sbodio, Tercero, Coutaz, & Martinez, 2002), have also been compared with rheological techniques and validated by Payne (1999, 2000). Moreover, Passos et al (1999) observed a decrease in the thermal conductivity of milk during coagulation using a heated thermistor and established a good prediction equation for rennet coagulation time.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we used rennet gels made at constant pH, temperature and CaCl 2 , to investigate the effect of changes in the final NaCl concentration (considering final NaCl concentration as natural Na expressed as NaCl plus NaCl added) and rennet concentration on the aggregation of renneted casein micelles and the gel development. The central level of rennet concentration was chosen as 0.028 RU·mL -1 milk, in agreement with the optimised level obtained by Sbodio et al (2002). Similarly, pH and temperature were set at 6.60 and 35 °C, respectively.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
“…The electric current was supplied by a power supply (6177C DC Current Source, Hewlett Packard, USA) with 0.03 resolution. Voltage drop, processed by a mathematical algorithm, was plotted as a function of time, according to Sbodio et al (2002).…”
Section: Coagulation Assaymentioning
confidence: 99%
“…Dos litros de leche tratada térmicamente con la adición de CaCl 2 y el ajuste correspondiente de pH, fue mantenida a temperatura constante de 38 °C durante el proceso de coagulación. Un sensor de platino 99% (Aldrich Chemical Company, Inc. Milwaukee, WI, USA) de 0,10 mm de diámetro y 110 mm de longitud fue usado para monitorear el proceso de formación del coágulo como describen previamente Hori (1985) y Sbodio et al (2002).…”
Section: Ensayo De La Coagulaciónunclassified